Pelatihan Teknik Cinematic sebagai Media Bantu Promosi Digital - Anas, Andi Sofyan; Fatimatuzahra, Fatimatuzahra; Hammad, Rifqi; Arfa, Muhammad; Latif, Kurniadin Abdul; Madani, Miftahul; Lestari, I Desak Ayu Adhia (LPPM Universitas Bumigora, 2023)
In the world of beauty service business, the increasingly competitive competition encourages entrepreneurs to improve the quality of their services and products so they can compete in the market. Salon Bricela, a beauty salon specifically for women, offers various types of grooming services to attract consumers. However, with the emergence of many salons and spas in the city of Mataram, Bricela Salon needs to find a different way to promote its products and increase its presence. One of the solutions chosen is to make promotional videos that use cinematic techniques to attract consumer interest. The purpose of this thesis is to make a promotional video that introduces Salon Bricela's Spa care products that are not well known in the wider community. The result of this research is a promotional video using Cinematic Techniques as a Media for Digital Promotion which displays the types of treatments and beauty products used in the Bricela salon. It is hoped that by using this technique, the promotional video for Bricela Salon will become more attractive and easily understood by consumers, so it can increase the existence of Bricela Salon in the city of Mataram.